2018
DOI: 10.1016/j.gexplo.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and preliminary risk assessment of road dust collected in Venice airport (Italy)

Abstract: Road dust is a non-exhaust source that can significantly contribute to atmospheric particulate by resuspension. Beside the issue of the overcoming of guidelines limits for the air quality, the characterization of this matrix is of crucially high interest for the inherent toxicity of resuspended particles, that can act as carriers of heavy metals and toxic-carcinogenic components.In this paper, road dust collected in the Venice international airport is characterized with a multi-technique approach in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…In the past, the attention of researchers was focused mainly on the role of gaseous pollutants on stone or mortar deteriorations, especially on sulphur dioxide [1]. However, in many cities of Europe, the levels of SO2 have been reduced while the huge increase in automobile traffic has promoted a considerable rise in the levels of ozone, nitrogen oxides and Total Suspended Particulate Matter [1,2], being aerosol derived from combustion processes the main cause of atmospheric pollution in urban environments after gaseous contamination [3]. This fact has generated a new air pollution scenario [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the attention of researchers was focused mainly on the role of gaseous pollutants on stone or mortar deteriorations, especially on sulphur dioxide [1]. However, in many cities of Europe, the levels of SO2 have been reduced while the huge increase in automobile traffic has promoted a considerable rise in the levels of ozone, nitrogen oxides and Total Suspended Particulate Matter [1,2], being aerosol derived from combustion processes the main cause of atmospheric pollution in urban environments after gaseous contamination [3]. This fact has generated a new air pollution scenario [1].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the formed particulates includes polymers and PTEs such as Zn, Mo, and Cu [6]. The observed increased amount of Zn is frequently associated with tire wear [65][66][67]. The extreme conditions to which tires are exposed on the runway may result in the contamination of airport soils by Zn.…”
Section: Resultsmentioning
confidence: 99%
“…Some other elements have also been proposed for the identification of PM emitted from brake systems (see Table 5). Valotto et al [119] studied the road dust collected in Venice mainland, Italy, and identified brake wear as a significant pollutant source in the monitored area, based on the higher concentrations of Cr, Fe, Mo, Sb and, to a lesser extent, of Mg, Co, Ni, Cu, Pb. Adamiec et al [10] noted the presence of Ti, Cr, and Cu, and recognized them as key tracers of brake wear emissions, in their samples collected from the motorway and urban roads in Poland.…”
Section: Source Apportionment: Trace Elements For Brake Wearmentioning
confidence: 99%